2022
DOI: 10.1016/j.cmi.2021.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of first-line treatment for chronic hepatitis B in China

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…Following adjustments based on the annual consumer price index (CPI), the costs of ETV and TAF became comparable. In contrast to international studies reporting TAF being 18.5%-56.4% more expensive than ETV in cost-utility analyses [22,23], the pharmaceutical cost of TAF in Taiwan is notably economical. Consequently, within the Taiwanese context, TAF presents the optimal cost-utility profile.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Following adjustments based on the annual consumer price index (CPI), the costs of ETV and TAF became comparable. In contrast to international studies reporting TAF being 18.5%-56.4% more expensive than ETV in cost-utility analyses [22,23], the pharmaceutical cost of TAF in Taiwan is notably economical. Consequently, within the Taiwanese context, TAF presents the optimal cost-utility profile.…”
Section: Discussioncontrasting
confidence: 64%
“…(b) Real-world medical costs for analysis: A distinctive facet of this study lies in the utilization of real-world medical costs for the analysis. By acknowledging the potential variability in outcomes from simulated cost-utility analyses of TAF for hepatitis B patients in different clinical scenarios [22,23], this study's reliance on real-world data provides a more authentic basis for evaluating the disparities in the actual costs and utility between TAF and ETV. (c) One-on-one comparison of cost-utility profiles: This study represents a pioneering effort in conducting a direct comparison of the cost-utility profiles of TAF and ETV.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the prevention and treatment of CHB, cost-effectiveness analysis is one of the commonly used methods, which has advantages such as easy understanding, easy decision-making, and avoiding ethical debates about using money as a measure of the value of human life. [ 24 28 ] Cost-effectiveness analysis of this study showed the CER of TAF group was similar of TDF group. After treatment, the adverse reactions included Kidney injury, nausea/vomiting.…”
Section: Discussionmentioning
confidence: 67%
“…Immunomodulators such as pegylated interferon alpha (PEG-IFNα), are currently considered to be the most effective antiviral therapy for clinical cure 1 . However, the uncertainty of the outcomes of interferon therapy, coupled with a substantial incidence of adverse reactions during treatment, the potential for relapse even after achieving clinical cure, the long treatment period, and the high cost, may all have an impact on patients’ physiological, psychological, and social functioning 4 6 . Previous studies of interferon therapy for CHB patients mainly focused on therapeutic efficacy, prognosis, and predictive indicators 7 , with little attention paid to psychosocial aspects.…”
Section: Introductionmentioning
confidence: 99%